Autonomia, automazione, mediazione. Alcune note critiche sull’etica dei veicoli a guida autonoma - Fossa, Fabio (Filosofia Morale/Moral Philosophy, 2024)
Autonomy, automation, mediation. Some critical notes on the ethics of self-driving cars This paper discusses how automated vehicles ambiguously mediate the ethical value of human autonomy. By offering a criticism of the hype surrounding the issue, it suggests that different forms of driving automation mediate different aspects of human autonomy differently. Its promotion and protection can only be incompletely achieved through a narrow focus on the design and deployment of automated vehicles. Therefore, a broader focus on transportation ethics is required.